2021
DOI: 10.1186/s10086-020-01937-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chinese fast-growing trees and the effect of alternating lamination using mixed-species eucalyptus and poplar veneers

Abstract: Over the past few decades, the sustainable forest area in China has increased remarkably, with 2400 million cubic meters of eucalyptus produced in 2018 in Guangxi which is the largest plantation area in China. In this study, the effect of alternating lamination using soft poplar veneers and hard eucalyptus veneers, on the mechanical properties of laminated veneer lumber (LVL), was examined. Eucalyptus and poplar veneers were imported from China to Japan to manufacture the LVL. For both eucalyptus and poplar ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…When the density of surface layer and core layer was similar, the density of surface layer had a weaker effect on the density of panel which was made from radial bamboo slices [26,27].…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…When the density of surface layer and core layer was similar, the density of surface layer had a weaker effect on the density of panel which was made from radial bamboo slices [26,27].…”
Section: Densitymentioning
confidence: 99%
“…It should be noted that the MOEeff of specimen ID layup in minor direction was in line with the requirement of national standard in the major direction, and that in major direction was in accordance with the national requirement in minor direction. This could be caused by the two-ply poplar veneers on the surface, whose textures were perpendicular to the major direction [26,32,33].…”
Section: Moeeff and Moreffmentioning
confidence: 99%
“…Adhesive failure is one of the main issues encountered during the production of Eucalyptus-based LVL. However, this issue can be ameliorated by alternating lamination using poplar and Eucalyptus veneers as demonstrated by Murata et al [77]. e authors found the alternating lamination using softer poplar veneers could reduce the quality variations of Eucalyptus and hence improved its variation in the modulus of elasticity.…”
Section: Lvlmentioning
confidence: 99%
“…In 1995, Baldwin compiled detailed information on the technological properties, production techniques, advantages, and disadvantages of LVL (Baldwin 1995). In today's world, there is a severe shortage of wood resources, which has led to a focus on utilizing fast-growing trees to supply wood for manufacturing wood products (Bal 2016;Murata et al 2021;Alamsyah et al 2023). In a study conducted by Prakash et al (2019), the feasibility of producing LVL from fast growing plantation timber (Melia dubia) was examined, with the conclusion that LVL could be utilized for door and window frame applications.…”
Section: Introductionmentioning
confidence: 99%